Searching of weekly cycles in the aerosol parameters of Antarctic atmosphere in comparison with Earth industrial regions - A.V. Soina; G.P. Milinevsky; Yu.M. Yampolsky (Ukrainian Antarctic Journal, 2017)
Objectives: (1) comparison of the 7-day variation of aerosol parameters of industrially developed regions of the Earth with weekly changes in the Antarcticа as an area with a minimum technogenic load; (2) test the anthropogenic nature hypothesis of 7-day variation of aerosol content in the atmosphere (weekend-effect), which was previously proposed by the authors on the research of global thunderstorm activity; (3) weekend changes have not been revealed in Antarctic region due to the neglect anthropogenic load in this area. The data from the aerosol international AERONET monitoring network was used to search for 7-day variations. Five-year aerosol optical thickness (AOT) data in two spectral channels of 440 and 870 nm for the 2009-2013 period were processed. The Ångström exponent was calculated from the measurements at these two wavelengths, and the precipitable water vapor data have been revealed from measurements in the spectral channels of 936 and 870 nm. We use the Antarctic AERONET stations data, as a “reference” values due to minimum anthropogenic load on the environment in this area. Data processing was performed by the epoch-superimposing method. As a result of the statistical analysis of aerosol parameters behavior in the atmosphere over the most industrially developed regions of Europe, North America and Asia, seven-day periodicity has been revealed, that confirms the increasing technogenic impact on the environment. The main conclusion of the work includes: (1) the weekend effect, previously found in the concentration of atmospheric aerosol for individual cities, is also manifested in the mean data of different monitoring stations of the studied regions (North America, Europe, Asia); (2) the 7-day cycle behavior in different parts of the world is similar for all aerosol parameters, when the maximum value is observed in the second half of the working week and at least on weekends; (3) in the Antarctic region as the area with the minimum of technogenic load, the weekend-effect was not found, which indicates the exclusively anthropogenic nature of weekly variations in the atmospheric aerosol parameters.